Open is not enough: design considerations for a networked data commons - Wilson, Anna; Hamilton, Hannah; Singh, Greg; McClenaghan, Ash; Lockley, Pat (Proceedings of the International Conference on Networked Learning, 2024)
Recently, researchers within the Networked Learning (NL) community have tried to (re)claim NL’s roots in critical pedagogy and (re)assert its commitment to social justice (Networked Learning Editorial Collective, 2021; 2021a). However, despite these avowed intentions, NL has also been criticised from within for “fail[ing] to take account of emancipatory struggles and political imperatives in society more broadly” (Networked Learning Editorial Collective, 2021a, p. 328). The suggestion is made to put NL “to work … to allow the concept of NL itself to become ‘networked’: to make connections, to interrelate, to transform, mutate, and hybridise in response to the pressing issues of our time” (Networked Learning Editorial Collective, 2021a, p. 359). In this paper, we take concepts from NL and put them “to work” in relation to the design of an informal digital learning environment – that is, a digital environment that lies outside of formal education provision, but that is intended to be a place where knowledge can be shared and circulated and where people encounter knowledge in ways that enable them to think, understand or act differently. The work was carried out in the context of a project aiming to develop design principles for an internet-based platform through people would be able to openly access, learn about and share publicly available data, using Scotland’s waste and re-use data as a case study. In this context, we plug NL into a theoretical and methodological design assemblage that connects concepts of openness, data literacy, (de)coloniality, and participatory design into new formations that we hope will allow these concepts to mutate and hybridise into something closer to the social justice ideals that NL claims.